Boron-calcium interaction in the growth ans mineral content of sweet pepper plants - Moreno Gómez, Tomás; Hernández-Pérez, Armando; Sandoval-Rangel, Alberto; Robledo-Torres, Valentín; Mendoza-Villarreal, Rosalinda; González Fuentes, José Antonio (Ecosistemas y Recursos Agropecuarios, 2021)
Boron (B) toxicity is an environmental restriction limiting crop productivity. The goal of this research work was to determine the influence of Calcium(Ca) in sweet pepper plants irrigated with high B concentrations. The assessed treatments included five B concentrations (0.5, 1.5, 3.0, 4.5 and 6.0 ppm) and three Ca concentrations (7, 9 and 11 meq L-1). Photosynthesis, plant height, root dry weight and total dry weight decreased as B concentration increased in the nutrient solution; however, B negative effect was lower as Ca concentration increased in thenutrient solution. High B concentrations affected root length and Ca increase did not show any positive effect. Furthermore, total N, P, K, Ca and Mg contents in sweet pepper plants decreased when B concentration increased; however, except for Mg, these decreases were lower when Ca concentration increased at nine (9) and eleven (11) meq L-1. Total B content in plants decreased when the concentration of this micronutrient increased in the solution; however, when Ca rate in the solution was higher than seven (7) meq L-1, B content experienced a sharper drop. Therefore, under B excess conditions, the growth and nutrient uptake of sweet pepper plantscan improve by increasing Ca concentration in the nutrient solution.